2015
DOI: 10.1016/j.jda.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Forwarding and optical indices of 4-regular circulant networks

Abstract: An all-to-all routing in a graph $G$ is a set of oriented paths of $G$, with exactly one path for each ordered pair of vertices. The load of an edge under an all-to-all routing $R$ is the number of times it is used (in either direction) by paths of $R$, and the maximum load of an edge is denoted by $\pi(G,R)$. The edge-forwarding index $\pi(G)$ is the minimum of $\pi(G,R)$ over all possible all-to-all routings $R$, and the arc-forwarding index $\overrightarrow{\pi}(G)$ is defined similarly by taking direction … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…In the part of path allocation, we aim to find a set of dipaths that minimizes the maximum link load; in the part of wavelength assignment, we aim to minimize the usage of wavelengths. Specifically, the minimum of the maximum link load over all possible routings is referred to as the forwarding index when link load is measured by the number of paths passing through it [11,12]. We refer to the minimum number of wavelengths, used to support simultaneous host-to-host communication, as the optical index.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the part of path allocation, we aim to find a set of dipaths that minimizes the maximum link load; in the part of wavelength assignment, we aim to minimize the usage of wavelengths. Specifically, the minimum of the maximum link load over all possible routings is referred to as the forwarding index when link load is measured by the number of paths passing through it [11,12]. We refer to the minimum number of wavelengths, used to support simultaneous host-to-host communication, as the optical index.…”
Section: Introductionmentioning
confidence: 99%
“…We refer to the minimum number of wavelengths, used to support simultaneous host-to-host communication, as the optical index. It has been shown that the optical index is naturally lower bounded by the forwarding index [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Various factors need to be considered in order to achieve high performance and low construction costs of an interconnection network. Among them, vertex-transitivity, small and fixed node degree, small diameter, recursive construction, existence of efficient routing algorithms are some of the desirable properties [10,13,18,21]. For example, networks with smaller diameters will lead to shorter data transmission delay.…”
Section: Introductionmentioning
confidence: 99%
“…We give approximation algorithms for the corresponding problems of the forwarding indices and optical indices with a small constant performance ratio. Our results on the family of circulant graphs of degree 4 are published in [3].The family of recursive cubes of rings has received a lot of attention for communication networks [10], but many aspects of them have remained unknown. We study this family of graphs by redefining each of them as a Cayley graph on the semidirect product of an elementary abelian group by a cyclic group in order to facilitate the study of them by using algebraic tools.…”
mentioning
confidence: 99%
“…We give approximation algorithms for the corresponding problems of the forwarding indices and optical indices with a small constant performance ratio. Our results on the family of circulant graphs of degree 4 are published in [3].…”
mentioning
confidence: 99%